Implementation of the performance management and development system in a Gauteng Provincial Department - Makhooa, Lirontso (My University, 2018)
The South African government identified the need for improved individual and organisational performance to deliver quality services to the citizens of the country. In 2003, the government introduced the performance management and development system (PMDS) to improve individual and organisational performance and, ultimately, achieve quality service delivery (Penceliah, 2012). This paper proposes to explore employees’ perceptions of the implementation of the PMDS in the Gauteng Department of Agriculture and Rural Development (GDARD) and the role of HRD. This study applied a qualitative research strategy and case study research design to conduct the empirical part of the research. Research participants were recruited through purposive sampling. A semi-structured interview was used to collect data from employees who are on salary levels four to twelve and assessed through the PMDS. Primary data was analysed using direct thematic content analysis. The findings in this research suggest that employees at the GDARD perceive the PMDS to be a tool to improve individual and, ultimately, organisational performance. The employees are particularly motivated by the financial element attached to the rewarding of excellent performance. Their perceptions confirms the reinforcement theory, which proclaims that rewarding good performance encourages employees to repeat the same behaviour. Furthermore, the findings in this research suggest that the role of human resource development (HRD) in GDARD is to ensure that the PMDS is implemented correctly. This research concludes that implementation of the system in the Department needs to be improved, and a collective effort is required from human resource development (HRD) directorate and senior management of GDARD.
Thesis presented in partial fulfilment for the degree of Master of Management (in the field of Public and Development Management) to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, November
Keywords: Perfomance--Management; Civil service--South Africa; Public administration; Employees--Rating of